Pulsed-Field Gel Electrophoresis Analysis of Salmonella enterica Serovar Enteritidis from Human and Food in Malaysia. (March 2022) - Hazis, N.H. Abd; Ahmad, N.; Zakaria, Z.; Hassan, L.; Sharif, Z.; Ali, R. Mohd; Husin, S. Amir; Sohaimi, N. Mohamed; Bakar, S. Abu; Bashiru, G.
Abstract : Purpose: Salmonella enterica serovar Enteritidis ( S . Enteritidis) is one of the most common serovars, associated with human salmonellosis worldwide and in Malaysia. Human S .Enteritidis cases are mostly associated with the consumption of poultry meat and contaminated eggs. However, there was limited data on the transmission of S . Enteritidis via the food chain in Malaysia. The objective of this study was to determine the genetic relatedness between S . Enteritidis strains isolated from human and food in central region of Peninsular Malaysia. Methods & Materials: A total of 53 S . Enteritidis strains from human and food samples were collected and processed. Serovar Enteritidis were determined based on the antigenic structure of both somatic (O) antigen, flagellar (H) and capsular (Vi) antigens using slide agglutination with commercially produced antisera according to the Kauffmann–White Scheme. All isolates were subjected to Pulsed-Field Gel Electrophoresis (PFGE) using Xba I restriction enzyme. PFGE results were analyzed by bioinformatic software (FPQuest). Cluster analysis of the Dice similarity co-efficient was based on the unweighted pair group method with arithmetic averages (UPGMA) and dendrogram was generated to describe the relationship among isolates. Results: PFGE analysis generated 27 unique patterns known as pulsotypes. Each pulsotype consisted of 9 to 13 DNA fragments with size ranging from 30kb to 1500kb. Cluster analysis based on a Dice Coefficient of 0.5 and a similarity index of 90% grouped the pulsotypes into 5 main clusters (A-E) whereas the remaining 8 pulsotypes were singletons. Cluster D consisted isolates from both human and food sources was the largest, most predominant and endemic in Malaysia. Conclusion: PFGE results showed that S . Enteritidis in this study were genetically heterogenous and diverse. Sharing a similar pulsotype between human and food isolates indicating the close genetic relationship between the two sources and suggested foods such as chicken meat and ready-eat-food do play a role as a vehicle in transmission of S . Enteritidis isolates to human.